2011
DOI: 10.1111/j.1440-1584.2011.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

The John Flynn Placement Program: Evidence for repeated rural exposure for medical students

Abstract: Longitudinal experiences, such as the JFPP, are positively influencing intention to enter the rural workforce but the impact of urban centric vocational training might be negating this impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 8 publications
0
52
0
Order By: Relevance
“…The quality screening process led to 40 studies being classified as ‘moderate’ and therefore were well reported but the study designs could have been better by applying; larger sample sizes, achieving higher consent/participant rates, reducing risk of selection and recall bias, multi-site programs, applying control groups, or being multi-strategy comparison programs [12, 3573]. …”
Section: Methodsmentioning
confidence: 99%
“…The quality screening process led to 40 studies being classified as ‘moderate’ and therefore were well reported but the study designs could have been better by applying; larger sample sizes, achieving higher consent/participant rates, reducing risk of selection and recall bias, multi-site programs, applying control groups, or being multi-strategy comparison programs [12, 3573]. …”
Section: Methodsmentioning
confidence: 99%
“…15 It demonstrates that the vast majority (90%) of students found their UDRH placement satisfying and that placement satisfaction is associated with changes in students' future practice intentions. It is encouraging that, on average, students who were less inclined or equivocal about rural practice before placement showed an increase in rural practice intention score afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…Of 21 different programs (described in 26 papers), 15 were primary care courses added to the conventional curriculum. [49][50][51][52][53][55][56][57][58][59][63][64][65][66][68][69][70][71][72] The remaining six programs were special curricula or medical schools focusing on primary care and/or rural health. 47,48,54,[60][61][62] , Contrary to the studies on clerkships, the most frequently studied outcomes of longitudinal programs were career choices after graduation (n=15).…”
Section: Impact Of Interventions On Primary Care Specialty Choicementioning
confidence: 99%